Kontaktzone: Das Definitionsproblem in Geisteswissenschaften - Petlyuchenko, Natalia V. (Moscow : Institute of World History; Alexander von Humbolt Stiftung / Foundation, 2017)
PRELIMINARY PUBLICATION OF CONFERENCE PROCEEDINGS
Petlyuchenko N. Kontaktzone: Das Definitionsproblem in Geisteswissenschaften / N. Petlyuchenko // Contact zones of Europe from the 3rd mill. BC to the 1st mill. AD : International Scientific Conference Humboldt Colleague (Moscow, 29 September – 2 October, 2017). - Moscow : Institute of World History; Alexander von Humbolt Stiftung / Foundation, 2017. - P. 110.
Keywords: Kontaktzone; Grenzgebiet; Grenzland; Frontier Society; Interaktion; Interkulturalität; Creoleness; Hybridität; Koine